Structural factors modulate the activity of antigenic poliovirus sequences expressed on hybrid hepatitis B surface antigen particles. - Delpeyroux, F (1990)
We have studied the functional expression of antigenic poliovirus fragments carried by various hybrid hepatitis B surface antigen (HBsAg) particles. Several constructions were made by using two different insertion sites in the HBsAg molecule (amino acid positions 50 and 113) and two different sequences, one derived from poliovirus type 1 (PV-1) and the other from PV-2. The inserted fragments each encompassed residues 93 to 103 of the capsid protein VP1, a segment which includes the linear part of the neutralization antigenic site 1 of the poliovirus. The antigenicity and immunogenicity of the hybrid particles were evaluated and compared in terms of poliovirus neutralization. A high level of antigenic and immunogenic activity of the PV-1 fragment was obtained by insertion at position 113 but not at position 50 of HBsAg. However, a cooperative effect was observed when two PV-1 fragments were inserted at both positions of the same HBsAg molecule. Antibodies elicited by the PV-2 fragment inserted at amino acid position 113 did not bind or neutralize the corresponding poliovirus strain. They did, however, bind a chimeric poliovirus in which the homologous antigenic fragment of PV-1 had been replaced by that of PV-2. The only virions that were neutralized by these antibodies were certain mutants carrying amino acid substitutions within the PV-2 fragment. These results show that position, constraints from the carrier protein, and nature of the inserted sequences are critically important in favoring or limiting the expression of antigenic fragments as viral neutralization immunogens.